Fostering partnerships: an autoethnographic study of collaboration between a hearing, signing teacher of the deaf and two American Sign Language interpreters - Willhite, Danielle (Dani) (My University, 2025)
As the population of deaf and hard-of-hearing (DHH) students in mainstream classrooms continues to grow (Luckner & Muir, 2001b; Stinson & Antia, 1999), effective collaboration among specialized professionals is increasingly vital (Antia & Kreimeyer, 2001b; Cogen & Cokely, 2015). This critical-interpretive autoethnographic study examined my experiences as a hearing, signing teacher of the deaf (TOD) working with two American Sign Language (ASL) interpreters within a self-contained DHH science classroom. Grounded in Tuckman’s (1965; Tuckman & Jensen, 1977) stages of group development, this research explored how our teamwork unfolded through the stages of forming, storming, norming, performing, and adjourning (Bonebright, 2010). Data collection employed triangulation (Creswell & Poth, 2018; Denzin, 1978) through reflective video journals, structured interpreter interviews, and document analysis of job descriptions and professional development records (Schick, 2007; Seal, 2004). Findings revealed that strong rapport and shared signing fluency supported smooth norming and performing, and role ambiguity, mismatched preparation, and feedback tensions emerged during storming and adjourning, highlighting the emotional labor involved in navigating daily collaboration. Divergences between my perspective and the interpreters’ insights exposed systemic barriers and the need for clearer role negotiation and joint professional learning (Cogen & Cokely, 2015; M. B. Smith & Ramsey, 2010). By situating these personal reflections within broader cultural and institutional contexts, I offered insights that illuminate the complexities of role clarity and teamwork and highlight ways to foster more equitable collaboration that can support improved educational access for DHH students in inclusive settings (Antia et al., 2002).
Keywords: ASL interpreters; Bilingual-bicultural (Bi-Bi) program; Comprehensive teacher preparation program; Critical-interpretive autoethnography; Deaf and hard of hearing (DHH); Deaf education; Language deprivation; Language modality; Listening and spoken language (LSL) program; Reflexivity; Role clarity; Self-contained classroom; Teamwork; Tuckman’s stages of group development